Ceramah Perundang-Undangan Transportasi Sebagai Upaya Mewujudkan Tertib Lalu Lintas di Jalan Raya - Oky Dedy Wijaya; Fibia Sentauri Cahyaningrum; Abdun Nafi Kurniawan; Moch. Wildan Makhrus; Yudhistira Wahyu Pambudi (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Public awareness of traffic order is still very worrying. This can be seen from the many violations while driving and the existence of fines from the traffic police, as evidenced by the ticket certificates received by the public. In addition to traffic violations, there are also many traffic accidents that occur due to people's ignorance in complying with applicable traffic regulations. These violations include: disobeying traffic signs, such as running a red light, not wearing an Indonesian National Standard helmet, and not equipping a vehicle such as not using a rearview mirror and not paying attention to vehicle lights (for example brakes) and lights turn off. These violations are usually committed not only by people who are old enough to drive a vehicle, but most are also committed by underage students. Based on these problems, the community service team gave a lecture on transportation legislation at SMA Muhammadiyah 4 Lamongan in an effort to increase awareness of orderly traffic to reduce accidents for students and the general public.